Gaya bahasa analogi pada lirik-lirik lagu karya Louane - Salsabila; Ratna; Ekowati, Sri Harini (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2022)
Abstract:This study aims to find out what types of analogy language styles are contained in Louane's song lyrics and how the analogy language style is represented in it. The approach used is descriptive qualitative, with the data collection method is to see notes. Meanwhile, the data analysis technique refers to the three stages of Sugiyono (2008), namely: the data reduction stage, the data presentation stage, and the data withdrawal or verification stage. The data sources used are the lyrics of Louane's song entitled